Exploring EKC, trends of growth patterns and air pollutants concentration level in Malaysia: A Nemerow Index Approach - Bekhet H.A. (Institute of Physics Publishing, 2023)
The present study examines an Environmental Kuznets Curve (EKC) hypothesis by analyzing annual data of air pollutants concentartion and per capita GDP as economic indicator over the (1996-2010) period in Malaysia. Nemerow Index Approach (I) used to generate a measures of air pollution. The results show that ambient air quality indicators supports the EKC hypothesis which stated that pollution levels increase as a country develops, but begin to decrease as rising incomes pass beyond a turning poin. Also, the I result is justifying that most pollutants are showing value less than 1. Published under licence by IOP Publishing Ltd.